Trousseaus syndrome due to asymptomatic pancreatic adenocarcinoma - Murinello,António (2013)
The authors report a case of Trousseaus syndrome presenting in a previously asymptomatic 58-year-old man diagnosed with pancreatic adenocarcinoma and liver metástases during a workup prompted by migratory venous thrombosis and pulmonary embolism. It was followed by an ischaemic stroke that occurred while the patient was just one day off anticoagulante therapy with low-molecular-weight heparin to allow for liver and pancreatic biopsies. Trousseaus syndrome is defined by recurrent or migratory venous thrombosis, arterial embolism caused by non-bacterial thrombotic endocarditis, or both, in patients with underlying malignancy. Treatment relies on the lifelong administration of heparin, and its interruption - however brief - may promote new thrombotic events.